Optimasi Rute Pengiriman pada CV. X Menggunakan Metode Evolutionary Algorithm - Setiadi Yulianto; I Gede Agus Widyadana; Nova Sepadyati (Jurnal Titra, 2022)
CV. X is an ice cube distributor. The company faced a problem that ice cube distribution time ussually longer than time window that has been set by the company. This research is focused on minimization delivery time therefore the total delivery time will not exceed the time window. Currently, the company operates two cars and two treecycle motorbikes. Every vehicle has more than one route every day. Therefore this research problem is Vehicle Routing Problem With Time Window. This problem is solved using the Evolutionary Algorithm method in Microsoft Excel software. The proposed routes can reduce delivery time on two different days by 9.85% and 4.02% for cars, as well as 9.85% and 11.8% on treecycle motorbikes.